Why is self-service technology (SST) unpopular? Extending the IS success model. Issue 4 (17th August 2018) - Lian, Jiunn-Woei
Abstract : Purpose: Self-service technology (SST) has become popular in many areas, but consumers from many countries still prefer human-provided services. Why is this so? The purpose of this paper is to understand the possible reasons by integrating two perspectives: personal characteristics marketing and the information systems success model (IS success model). Design/methodology/approach: The authors propose an integrated model and conduct an empirical questionnaire survey which generates a total of 345 valid responses. Findings: The authors find that personal technology anxiety and the need for interpersonal interaction are critical factors that affect SST usage continuance intention. Furthermore, personal technology anxiety affects the consumer's perception of the quality of both the information and the SST system itself, which determines the level of satisfaction and the intention to continue to use the system. Second, the IS success model perspective reveals that the following factors determine the level of perceived satisfaction with SST: information quality, system quality, enjoyment and design. However, only information quality and system quality affect the intention to continue SST usage. The authors also find that satisfaction and the need for interpersonal interaction also determine the SST usage continuance intention. Originality/value: The IS success model is found to be helpful in understanding the underlying reasons for this. To aid in the development of successful future SSTs, these findings can be referenced by countries in which SST is not so popular. Our proposed model further enhances the theoretical development of the IS success model.